Reconsidering Mullā Ṣadrā’s Anthropological Tenets in His Theory of Bodily Resurrection - Mohammad Kazem Forghani; Majid Taghinejat; Amir Hosein Soleimany (پژوهشنامه فلسفه دین, 2018)
The philosophical explanation of bodily resurrection is one of Mullā Ṣadrā’s philosophical innovations. He has illustrated this theory in al-Shawāhid al-Rububiyyah, al-Mabda‘ wa’l-Ma‘ad, al-Hikmat al-Muta'ālyah, Zad al-Musafir, Mafatih al-Ghayb and ‘Arshiyyah as 6-12 principles. By investigating these principles, we can identify a number of them which include other implicit principles. A precise enumeration will result in over 150 principles, either theological, anthropological, epistemological or ontological. In this paper, Mullā Ṣadrā’s anthropological tenets are extracted and presented as 53 immediate and 35 remote principles. Furthermore, the immediate principles are classified into four categories: (1) the soul-body relation principles, which establish the tautology of the soul and the body; (2) the principles governing the imaginative forms present in the Afterlife, which indicate that the human bodies in the Afterlife are imaginative and not material, (3) the principles concerned with the difference of the human souls present in the Afterlife, which introduce the different types of Afterlife for different souls, (4) the principles concerned with Substantial motion and death (i.e. the bridge between worlds), which demonstrate the nature of moving across worlds and entering the Afterlife